A Conceptual Framework for Studying the Relationship between the Total Quality Management and Food Safety Management on the Organizational Performance in the Thai Food Industry - Thiakthum, Suwimon; Pianthong, Nalin (Engineering, Technology & Applied Science Research, 2025)
The integration of Total Quality Management (TQM) and Food Safety Management (FSM) has become essential for enhancing the operational performance and ensuring the product quality in the Thai food industry. This study proposes and validates a conceptual framework linking key TQM and FSM practices to organizational performance. Data were gathered from 304 ISO 9001 and ISO 22000-certified companies across multiple sectors, using structured questionnaires and stratified random sampling. Structural Equation Modeling (SEM) was applied to examine both the direct and indirect effects. The results demonstrate that TQM significantly influences both the FSM practices and organizational performance, while FSM also exerts a positive mediating effect. Significant barriers identified include the limited knowledge, insufficient commitment, and a lack of internal training. These findings highlight the strategic importance of integrated management systems for improving the quality, compliance, and competitive advantage in the food sector.